Post-jökulhlaup geomorphic evolution of the Gígjökull Basin, Iceland - D. Harrison; N. Ross; A. J. Russell; S. A. Dunning (Annals of Glaciology, 2019)
How landscapes respond to, and evolve from, large jökulhlaups (glacial outburst floods) is poorly constrained due to limited observations and detailed monitoring. We investigate how melt of glacier ice transported and deposited by multiple jökulhlaups during the 2010 eruption of Eyjafjallajökull, Iceland, modified the volume and surface elevation of jökulhlaup deposits. Jökulhlaups generated by the eruption deposited large volumes of sediment and ice, causing significant geomorphic change in the Gígjökull proglacial basin over a 4-week period. Observation of these events enabled robust constraints on the physical properties of the floods which informs our understanding of the deposits. Using ground-based LiDAR, GPS observations and the satellite-image-derived ArcticDEMs, we quantify the post-depositional response of the 60 m-thick Gígjökull sediment package to the meltout of buried ice and other geomorphic processes. Between 2010 and 2016, total deposit volume reduced by −0.95 × 106 m3 a−1, with significant surface lowering of up to 1.88 m a−1. Surface lowering and volumetric loss of the deposits is attributed to three factors: (i) meltout of ice deposited by the jökulhlaups; (ii) rapid melting of the buried Gígjökull glacier snout; and (iii) incision of the proglacial meltwater system into the jökulhlaup deposits.